어린이급식관리지원센터에서 제공하는 어린이집 식단의 식품군 및 음식군 다양성에 관한 기술연구 - 강연록; 임경숙; 김형숙; Youn-Rok Kang; Kyeong-Sook Lim; Hyung-Sook Kim (Korean journal of community nutrition, 2023)
Objectives: This study aimed to analyze menu patterns and food group diversity in daycare centers managed by the Center for Children's Foodservice Management in South Korea. Methods: Data from 18 Center for Children's Foodservice Management centers across various provinces (excluding Jeju Island) were analyzed. We examined 8,796 meals served in February, May, August, and December 2021, focusing on seasonal lunch and snack menus for children aged 3-5. Foods were categorized into 19 groups for lunch and 21 for snacks. The frequency of food groups and dietary patterns were assessed using the Dietary Diversity Score. Analyses were conducted using Excel 2016 and IBM SPSS Statistics version 28. Results: Most lunch menus (89%) included five menu items, with a ratio of grain, meat, and vegetables at 88%. Snack menus typically had one item (57%), with significantly more items in the afternoon compared to the morning (P < 0.001). Regarding snack patterns, 75.2% of morning snacks and 61.1% of afternoon snacks contained only one solid food and drink (P < 0.001). Fruit and milk (22.4%) was the most prevalent pattern in morning snacks, while grain and milk (31%) dominated afternoon snacks (P < 0.001). Only 48% of daycare center menus (all snacks and lunch) included all five food groups (grain, meat, vegetables, fruit, and milk). Notably, only 83% included milk and 57% included fruit. Conclusions: These findings highlight the need to improve food variety and diversity in the Center for Children's Foodservice Management-managed daycare center menus. Developing more detailed guidelines for menu structure and food composition is crucial to ensure children receive balanced and diverse nutrition.